Editable texture map generation and optimization technique for 3D visualization presentation. Issue 3 (4th May 2018) - Wu, Tsung-Chien; Lai, Jiing-Yih; Phothong, Watchama; Wang, Douglas W.; Liao, Chao-Yaug; Lee, Ju-Yi
ABSTRACT: The mesh parameterization method has been widely used in computational geometry. It maps a three-dimensional (3D) model onto the parametric (UV) domain, on which various applications can be developed, such as texture mapping. The texture mapping technique is commonly used to create the 3D color model of an object by combining a 3D model with the object's texture map. However, the resolution and quality of the texture on the color model is important and requires careful consideration. The purpose of this study is to develop an integrated method for generating the 3D color model of an object based on the conformal mesh parameterization and a technique for direct texture mapping from the object images. Furthermore, an optimization process in texture mapping is developed to maintain the photo consistency at the transition of different images on the 3D color model. The proposed 3D color model is integrated with a 3D visualization method for a new easier and smoother presentation mode for 3D product presentation in e-commerce applications. Several realistic examples are presented to demonstrate the feasibility of the proposed method. GRAPHICAL ABSTRACT: